2008
DOI: 10.1080/15376510801891286
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of the Toxicogenomics and the Genotoxic Potential of a Cationic Lipid-Based Gene Delivery Nanosystem in Human Alveolar Epithelial A549 Cells

Abstract: Viral and nonviral vectors have been widely used in gene therapy as delivery reagents for nucleic acids. Toxicity with viral vectors has increasingly led to the search for suitable nonviral vectors, such as cationic lipids/polymers, as potentially safer alternatives. However, little is known about the genomic toxicity of these delivery systems in target cells/tissues. In the current investigation, we report on the toxicogenomics and genotoxicity of cationic lipid Oligofectamine (OF) nanosystems in human alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…From another viewpoint the individual effect of the carriers can be cut off into two categories (i.e., early and late impacts). For example, we have observed that most of the cationic gene delivery systems (e.g., linear and branched polyethylenimine (PEI), cationic lipids and dendrimers) are able to induce gene expression changes intrinsically (Hollins et al, 2007;Omidi et al, 2005b;Omidi, 2008). The determination of the early effects of a gene delivery system appears to be quite easy; however investigation on the late effects in a course of time is a cost demanding and time consuming trial.…”
Section: Genomic Impacts Of Gene Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…From another viewpoint the individual effect of the carriers can be cut off into two categories (i.e., early and late impacts). For example, we have observed that most of the cationic gene delivery systems (e.g., linear and branched polyethylenimine (PEI), cationic lipids and dendrimers) are able to induce gene expression changes intrinsically (Hollins et al, 2007;Omidi et al, 2005b;Omidi, 2008). The determination of the early effects of a gene delivery system appears to be quite easy; however investigation on the late effects in a course of time is a cost demanding and time consuming trial.…”
Section: Genomic Impacts Of Gene Delivery Systemsmentioning
confidence: 99%
“…Thus, there has been an increasing interest in design of delivery vehicles which are capable of delivering drugs (of any origin) inside cancer cells that is now an issue in design of molecular Trojan horses (Kim et al, 2008;Portney & Ozkan, 2006;Sawant et al, 2006). It has been revealed that most gene delivery systems can nonspecifically induce alterations in the gene expression profile of the target cells (Omidi et al, 2005a); an impact which is either parallel with the therapeutic purpose or contrary to it or even null. From another viewpoint the individual effect of the carriers can be cut off into two categories (i.e., early and late impacts).…”
Section: Genomic Impacts Of Gene Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, no substantial information is available about the genomic signature of the cationic delivery systems. We have previously investigated the potential of the commercially available nonviral vectors (e.g., Polyamidoamine (PAMAM) dendrimers such as Polyfect™ (PF) and Superfect™ (SF)) and lipids (e.g., Lipofectin™ (LF) and Oligofectamine ™ (OF)) on global gene expression within human epithelial A431 and A549 cells by exploiting the cDNA microarray technology (Barar et al, 2009;Omidi et al, 2003;Omidi et al, 2005a;Omidi et al, 2005b;Omidi et al, 2008). These investigations revealed occurrence of inadvertent nonspecific gene expression changes within target cells upon treatments with these cationic gene delivery nanosystems.…”
Section: Gene Therapy Challenges and Dilemmasmentioning
confidence: 99%
“…The aminoallyle-dUTP-cDNA is then labeled with cyanine dye (e.g., Cy3 or Cy5). The Cy3 and Cy5 labeled aminoallyle-dUTPcDNA from UT and T samples are hybridized on a single glass array, which is subjected to several washing steps, scanning with an appropriate scanner (e.g., using RS Reloaded™, TECAN, Switzerland) and data mining (e.g., using GeneMath™ software; Applied Maths, Sint-Martens-Lathem, Belgium); for detailed information reader is directed to see (Hegde et al, 2000;Omidi et al, 2005b;Omidi et al, 2008). For microarray analysis, significantly upregulated and/or downregulated genes can be identified using traditional method (gene expression changes with a fixed cutoff threshold usually in 2 fold) to infer significance differences (i.e., the so called "fold change method").…”
Section: Dna Microarray Technologymentioning
confidence: 99%